Gospel hall assemblies 1889-1994 the Brethren in Barbados - Catwell, Sylvan R. (St George, Barbados Sylvan R. Catwell, 1995)
Includes bibliographical references, maps, photographs, etc.
Keywords: Brethren movement -- history -- Barbados